The Role of Chloroquine Phosphate on Acute Phase Reactant Proteins in Patients with Knee Osteoarthritis - S. Saleh, Eman; M.Turki, Kismet; H.Al-Osami, Mohammed (Iraqi Journal of Pharmaceutical Sciences, 2017)
The acute phase response is a major pathophysiologic phenomenon that accompanies inflammation whether acute or chronic. Complement (C3 and C4) and C - reactive protein (CRP) are positive acute phase proteins (+ ve APPs ). Their production takes place in hepatocyte and the blood concentration of these parameters are increased in osteoarthritis (OA). Chloroquine (CQ) is a diprotic weak base traditionally used to treat malaria. Recently the phosphate salt of CQ is used to decrease this type of (+ve APPs) . In this study, patients who suffered from knee osteoarthritis (KOA) are treated with oral dosage form of chloroquine phosphate (CQP) for one month, twice daily. Our results demonstrate that CQP improves the patient status by decreasing complement and C-reactive protein in blood. Key words: Chloroquine , knee osteoarthritis , acute phase proteins , complement , C-reactive protein.